2009
DOI: 10.1038/embor.2009.127
|View full text |Cite
|
Sign up to set email alerts
|

HAT–HDAC interplay modulates global histone H3K14 acetylation in gene‐coding regions during stress

Abstract: Histone acetylation and deacetylation are important for gene regulation. The histone acetyltransferase, Gcn5, is an activator of transcriptional initiation that is recruited to gene promoters. Here, we map genome-wide Gcn5 occupancy and histone H3K14ac at high resolution. Gcn5 is predominantly localized to coding regions of highly transcribed genes, where it collaborates antagonistically with the class-II histone deacetylase, Clr3, to modulate H3K14ac levels and transcriptional elongation. An interplay between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
81
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 30 publications
5
81
0
Order By: Relevance
“…Although Gcn5 is broadly enriched across highly transcribed genes in yeast (49), Gcn5-dependent acetylation patterns differ between gene promoters and coding regions (20,49). For example, both H3K9 and H3K14 acetylation can be catalyzed by Gcn5 in vivo, but high-resolution ChIP-sequencing data show that H3K9 acetylation is narrowly limited to promoter regions (20), whereas H3K14 acetylation spreads across gene bodies as well (49). How can the same enzyme generate different acetylation patterns?…”
Section: Discussionmentioning
confidence: 99%
“…Although Gcn5 is broadly enriched across highly transcribed genes in yeast (49), Gcn5-dependent acetylation patterns differ between gene promoters and coding regions (20,49). For example, both H3K9 and H3K14 acetylation can be catalyzed by Gcn5 in vivo, but high-resolution ChIP-sequencing data show that H3K9 acetylation is narrowly limited to promoter regions (20), whereas H3K14 acetylation spreads across gene bodies as well (49). How can the same enzyme generate different acetylation patterns?…”
Section: Discussionmentioning
confidence: 99%
“…Given that KAT2A increases histone H3K9/K14 acetylation (H3K9/K14ac) and accessibility of factors promoting transcription (33,41,42), we speculated that KAT2A is recruited to DDIT3⅐phospho-JUN complex via physical interaction with DDIT3 at the AP-1 binding site (Ϫ304/Ϫ298) in the TNFRSF10A promoter region, leading to acetylation of H3K9/ K14 and further enhancement of TNFRSF10A transcription. To verify this hypothesis, we performed ChIP experiments using anti-H3K9/K14ac antibody in the H1792 cell lysates after treatment with TG (1 M) or Tm (1 M) for 12 h. We found that the antibody against H3K9/K14ac captured the AP-1 binding site region of human TNFRSF10A promoter, and the quantity of PCR product containing the AP-1 binding site was increased in cell lysate prepared from TG-or Tm-treated H1792 cells, respectively (Fig.…”
Section: Ddit3 and Tnfrsf10a Expressions Are Up-regulated By Ermentioning
confidence: 99%
“…However, recent studies in yeast revealed that only a fraction of bound genes is misregulated upon deletion of SAGA subunits, and, conversely, only a fraction of misregulated genes is bound by the corresponding subunits (Lenstra et al 2011;Venters et al 2011;Lenstra and Holstege 2012). Furthermore, a wider distribution of the complex is suggested by chromatin immunoprecipitation (ChIP) experiments on a few model genes in yeast that also detected SAGA in the coding region and by ChIP-coupled high-throughput sequencing (ChIP-seq) analyses in flies that revealed a colocalization of SAGA with RNA polymerase II (Pol II) in the body of a subset of genes (Govind et al 2007;Johnsson et al 2009;Weake et al 2011). In addition to its gene-specific regulatory role, it has been proposed that SAGA acetylates histones throughout the genome in a global and untargeted manner (Vogelauer et al 2000).…”
mentioning
confidence: 99%